Status of adult outpatients with congenital heart disease in Japan: The Japanese Network of Cardiovascular Departments for Adult Congenital Heart Disease Registry. Issue 6 (December 2022) - Yao, Atsushi; Inuzuka, Ryo; Mizuno, Atsushi; Iwano, Hiroyuki; Tatebe, Shunsuke; Tsukamoto, Yasumasa; Sakamoto, Ichiro; Watanabe, Hiroyuki; Fukuda, Nobuyuki; Takechi, Fumie; Adachi, Shiro; Akazawa, Yusuke; et al.
Abstract: Background: The Japanese Network of Cardiovascular Departments for Adult Congenital Heart Disease (JNCVD-ACHD) was founded in 2011 for the lifelong care of adult patients with congenital heart disease (ACHD patients). This network maintains the first Japanese ACHD registry. Methods and results: From 2011 to 2019, the JNCVD-ACHD registered 54 institutions providing specialized care for ACHD patients in 32 of the 47 prefectures in Japan. The registry collected data on the disease profile for 24, 048 patients from 50 institutions and the patient characteristics for 9743 patients from 24 institutions. The most common ACHDs were atrial septal defect (20.5 %), ventricular septal defect (20.5 %), tetralogy of Fallot (12.9 %), and univentricular heart (UVH)/single ventricle (SV; 6.6 %). ACHD patients without biventricular repair accounted for 37.0 % of the population. Also examined were the serious anatomical and/or pathophysiological disorders such as pulmonary arterial hypertension (3.0 %) including Eisenmenger syndrome (1.2 %), systemic right ventricle under biventricular circulation (sRV-2VC; 2.8 %), and Fontan physiology (6.0 %). The sRV-2VC cases comprised congenitally corrected transposition of the great arteries without anatomical repair (61.9 %) and transposition of the great arteries with atrial switching surgery (38.1 %). The primary etiology (86.4 %) for Fontan physiology was UVH/SV. In addition, developmental/chromosomal/genetic disorders were heterotaxy syndromes (asplenia, 0.9 %; polysplenia, 0.7 %), trisomy 21 (4.0 %), 22q11.2 deletion (0.9 %), Turner syndrome (0.2 %), and Marfan syndrome (1.1 %). Conclusions: Although the specific management of ACHD has systematically progressed in Japan, this approach is still evolving. For ideal ACHD care, the prospective goals for the JNCVD-ACHD are to create local networks and provide a resource for multicenter clinical trials to support evidence-based practice. Graphical abstract: Unlabelled Image Highlights: JNCVD-ACHD registers 54 centers for adult congenital heart disease (CHD). JNCVD-ACHD establishes lifelong care for adults with CHD. The JNCVD-ACHD patient registry shows characteristics and challenges of adult CHD. JNCVD-ACHD is a resource for multi-center clinical trials for adult CHD care.